Fiber to the brain [brain surgery]. - Jones, W.D.
This paper describes a promising new procedure developed by researchers from the New York University Medical Center, the Massachussets Institute of Technology, and the University of Tokyo to perform brain surgery via nanotechnology. The procedure involves attaching electrodes to small clusters of brain cells using the cardiovascular system as the conduit through which wires are threaded. This procedure does not require surgeons to break through the skull, which could damage healthy brain tissues and expose patients to infection.
Keywords: Blood vessels; Brain surgery; Brain tissue damage; Cardiovascular system; Conducting polymer materials; Electrodes; Human brain; Medical diagnostics; Nanotechnology; Polymer nanowires